AMBIGUITY IN THE MANAGEMENT OF ZAKAT FUNDS IN ISLAMIC BANKING BASED ON MAQASHID SHARIA AND SUSTAINABLE DEVELOPMENT GOALS (A PHENOMENOLOGICAL STUDY OF ZAKAT FUND MANAGEMENT AT BANK SYARIAH INDONESIA) - Ratulaah, Gita Ariesta Putri; Kwarto, Febrian (Ridwan Institute, 2025)
Zakat as a Mahdhah worship has maqashid Zakat to meet the emergency needs of Mustahik which consists of 8 Asnaf. Zakat is a tool to carry out humanitarian programs that are sustainable in nature in addition to emergency needs (needs that must be met at that time). The purpose of this research is to identify the sources of ambiguity in the management of Muslim funds and to explore how these perspectives can function harmoniously. The research triangulation was carried out by looking at the compatibility of the data obtained from the Forum Group Discussion (FGD) with the Depth Interview used. The results of the study indicate that there are differences in understanding of Zakat innovation, especially related to income Zakat and corporate Zakat. The integration of programs sourced from Zakat funds and CSR funds is based on the needs and responsibilities of companies to fulfill maqashid Sharia and sustainable development.